Detection of serum melanoma‐associated antigen D4 in patients with squamous cell carcinoma of the esophagus. Issue 6 (8th May 2015) - Oya, H.; Kanda, M.; Koike, M.; Iwata, N.; Niwa, Y.; Shimizu, D.; Takami, H.; Sueoka, S.; Hashimoto, R.; Ezaka, K.; Nomoto, S.; Yamada, S.; et al.
Abstract : Summary: Despite improvements in surgical techniques, perioperative management, and multidisciplinary therapy, treatment outcomes of patients with esophageal squamous cell carcinoma (ESCC) remain poor. Therefore, development of novel molecular biomarkers, which either predict patient survival or become therapeutic targets, is urgently required. In the present study, to facilitate early detection of ESCC and predict its clinical course, we investigated the relationship of the serum level of melanoma‐associated antigen (MAGE)‐D4 to patients' clinicopathological characteristics. Using quantitative real‐time reverse transcription‐polymerase chain reaction and enzyme‐linked immunosorbent assays, we determined the levels of MAGE ‐ D 4 mRNA and protein in cell lysates and conditioned medium of cultures, respectively, of nine ESCC cell lines. Further, we determined MAGE‐D4 levels in serum samples collected from 44 patients with ESCC who underwent radical esophagectomy without neoadjuvant therapy as well as from 40 healthy volunteers. Samples of conditioned medium and cell lysates contained comparable levels of MAGE‐D4 that correlated closely with the levels of MAGE ‐ D 4 mRNA. Preoperative MAGE‐D4 levels in the sera of 44 patients with ESCC, which varied from 0 to 2, 354 pg/mL (314 ± 505 pg/mL, mean ± standard deviation), were significantly higher compared with those of healthy volunteers. By setting the cutoff at the highest value for healthy volunteers (50 pg/mL), the MAGE‐D4‐positive group of patients was more likely to have shorter disease‐specific and disease‐free survival compared with those of the MAGE‐D4‐negative group, although the differences were not statistically significant. Our results indicate that the elevation of preoperative serum MAGE‐D4 levels in some patients with ESCC was possibly caused by excess production of MAGE‐D4 by tumor cells followed by its release into the circulation. Clinical implications of serum MAGE‐D4 levels should be validated in a large population of patients with ESCC.